Primary squamous cell carcinoma of the stomach: a case report and literature review - Gao, Shengqiang (Int J Clin Exp Pathol, 2015)
Primary squamous cell carcinoma (SCC) of the stomach is rare. Its pathogenesis is also unclear and there are conflicting reports about it in the past. Only about 100 cases have been reported so far in the literature. The current study discusses a new case of gastric squamous cell carcinoma, from a 50-year-old Chinese male patient diagnosed via subtotal gastrectomy with Roux-en-Y reconstruction and D2 lymphadenectomy. In the stomach, an ulcerated mass in the antrum, measuring 12×8×6 cm, was observed. Further, pathological examination of the resected specimen revealed a well-differentiated SCC. Observations indicated tumor cell invasion into the serosa, and encroachment into perigastric regional lymph node. A follow-up abdominal CT scan three months later revealed tumor invasion into the ascending colon. We assume that this invaded mass was transferred from the gastric squamous cell carcinoma. Interestingly, the patient is still alive.